The Digital Advertising Strategy in order to Maintain Home Business Branding in The Times of Pandemic: Existed in The Times of Crisis - Purwaningwulan, Melly Maulin (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
Pandemic condition has test the stability of the brand that has been built by the company. This research aimed to in-depth-analyze the Digital Advertising Strategy in order to Maintain Home Business Branding in The Times of Pandemic: Existed in The Times of Crisis. The research was conducted with a qualitative approach. The most appropriate method for this research was descriptive. Data collection was conducted through observation and in-depth interviews. Research informant is a home businesses and the expert of marketing communication. The result showed that the most widely used digital advertising is Instagram. Instagram is used for branding because followers and interactions has not optimal yet. To increase sales of home business usually cooperate with online applications. The cooperation mechanism uses profit sharing or commission calculations as well as sales promotions. Home businesses that have more capital will use digital advertising to maintain sales with attractive promotions. The conclusion of this research is that the home businesses must be able to distinguish between marketing and branding, during a pandemic, digital advertising strategies are used to show the primacy of product benefits and add attributes to products related to the pandemic. This research has an impact on the development and selection of the right Digital Advertising Strategy for online businesses so that they can survive during and after a pandemic.